A diachronous record of metamorphism in metapelites of the Western Gneiss Region, Norway. (17th March 2022) - March, Samantha; Hand, Martin; Tamblyn, Renée; Carvalho, Bruna B.; Clark, Chris
Abstract: In this study, data from garnet‐kyanite metapelites in ultrahigh‐pressure (UHP) domains of the Western Gneiss Region (WGR), Norway, are presented. U–Pb geochronology and trace element compositions in zircon, monazite, apatite, rutile and garnet were acquired, and pressure–temperature ( P–T ) conditions were calculated using mineral equilibria forward modelling and Zr‐in‐rutile thermometry. Garnet‐kyanite gneiss from Ulsteinvik record a prograde evolution passing through 690–710°C and 9–11 kbar. Zircon and rutile age and thermometry data indicate these prograde conditions significantly pre‐date Silurian UHP subduction in the WGR and are interpreted to record early Caledonian subduction of continental‐derived allochthons. Minimum peak conditions in the Ulsteinvik metapelite occur at 28 kbar, constrained by an inferred garnet+kyanite+omphacite+muscovite+rutile+coesite+H2 O assemblage. The retrograde evolution passed through 740°C and 7 kbar, first recorded by the destruction of omphacite and followed by the partial replacement of kyanite and garnet by cordierite and spinel. Garnet‐kyanite metapelite from the diamond‐bearing Fjørtoft outcrop documents a polymetamorphic history, with garnet forming during the late Mesoproterozoic and limited preservation of high‐pressure Caledonian assemblages. Similar to the Ulsteinvik metapelite, zircon and rutile age data from the Fjørtoft metapelite also record pre‐Scandian Caledonian ages. Two potential tectonic scenarios are possible: (1) The samples were exhumed at different times during pre‐Scandian subduction of the Blåhø nappe, or (2) the samples do not share a history in the same nappe complex, instead the Ulsteinvik metapelite is a constituent of the Seve‐Blåhø Nappe, whilst the Fjørtoft metapelite shares its history within a separate nappe complex.